Green Intellectual Capital, Financial Performance, and Good Corporate Governance - Wati, Yenny; Irman, Mimelientesa; Yusrizal; Anton; Renaldo, Nicholas (Politeknik Caltex Riau, 2024)
This study aims to determine the impact of green intellectual capital on financial performance. Researchers employ good corporate governance as a moderating element in studies that examine the impact of green intellectual capital on financial performance. Companies listed on the Indonesia Stock Exchange (IDX) that participated in the PROPER assessment for the 2019-2022 term are the secondary data sources for this research. This study was carried out with WarpPLS, which employs the partial least squares data analysis method. Green intellectual capital improves financial performance. The impact of green intellectual capital on financial performance can be moderated by good corporate governance. Many investors and stakeholders are currently excited about the prospects of green intellectual capital and good corporate governance. Investors can pay attention to companies that reveal more information than is required by law as a prerequisite, allowing them to receive as much information as they need to decide whether to continue investing or start investing in lucrative companies or not. The government can conduct a thorough examination of the influence of green intellectual capital on corporate performance and assist in the development of new green intellectual capital rules.